Tradisi Nopen pada Resepsi Pernikahan Masyarakat Etnis Melayu dalam Mempertahankan Solidaritas Sosial di Kampung Menyumbung Kelurahan Ulak Jaya Kecamatan Sintang - Lira Miranda Kurniawan; Iwan Ramadhan; Patrsia Rahayu Utami; Agus Sikwan; Hadi Wiyono (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to describe (1). the role of the Nopen tradition in maintaining social solidarity in the Menyumbung village, Ulak Jaya sub-district, Sintang district, analyze (2). The Nopen tradition strengthens social ties in the Menyumbung village, Ulak Jaya sub-district, Sintang district, and analyze (3). The Nopen tradition reflects the values ​​of social solidarity in the Menyumbung village, Ulak Jaya sub-district, Sintang district. The approach used in this study is a qualitative approach with a descriptive research method. Data collection techniques use observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The analysis in this study used five informants. The results show the Nopen tradition at the wedding reception of the Malay ethnic community in maintaining social solidarity in the Menyumbung village, Ulak Jaya sub-district, Sintang district. The social solidarity formed in the Nopen tradition shows the theory of mechanical solidarity put forward by Emile Durkheim, solidarity is based on the similarity of values, norms, and traditions carried out together by the community. Community participation, regardless of age or social status, demonstrates emotional bonds, a sense of shared responsibility, and a sense of caring. Forms of social bonds include kinship, neighborhood ties, and complementary functional social ties. The values ​​of social solidarity, togetherness, mutual cooperation, and a sense of belonging are embedded in the implementation and stages of the Nopen tradition.